2008
DOI: 10.1093/cvr/cvp001
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C in heart failure: a therapeutic target?

Abstract: Heart failure (HF) afflicts about 5 million people and causes 300 000 deaths a year in the United States alone. An integral part of the pathogenesis of HF is cardiac remodelling, and the signalling events that regulate it are a subject of intense research. Cardiac remodelling is the sum of responses of the heart to causes of HF, such as ischaemia, myocardial infarction, volume and pressure overload, infection, inflammation, and mechanical injury. These responses, including cardiomyocyte hypertrophy, myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 94 publications
(102 reference statements)
2
130
0
Order By: Relevance
“…Our previous studies showed that short peptides derived from interaction sites between two proteins act as highly specific inhibitors and are effective drugs in basic research and in animal models of human diseases, such as myocardial infarction and hypertension (Inagaki et al, 2003;Palaniyandi et al, 2009;Qi et al, 2008). We proposed that because the peptides are flexible and represent part of the natural binding site, they may be superior and more selective inhibitors of PPI as compared with more rigid small molecules (Qvit and Mochly-Rosen, 2010;Ron and Mochly-Rosen, 1995;Souroujon and Mochly-Rosen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that short peptides derived from interaction sites between two proteins act as highly specific inhibitors and are effective drugs in basic research and in animal models of human diseases, such as myocardial infarction and hypertension (Inagaki et al, 2003;Palaniyandi et al, 2009;Qi et al, 2008). We proposed that because the peptides are flexible and represent part of the natural binding site, they may be superior and more selective inhibitors of PPI as compared with more rigid small molecules (Qvit and Mochly-Rosen, 2010;Ron and Mochly-Rosen, 1995;Souroujon and Mochly-Rosen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…PKC regulates many cardiac functions, including cardiomyocyte survival (20). To determine the activation status of conventional and novel PKC (nPKC) isozymes, we assessed the membrane and cytosolic localization of 3 representative PKC isozymes.…”
Section: Ca-rhoa Hearts Show No Alteration In Activation Of Akt Fakmentioning
confidence: 99%
“…A fundamental role of PKC isoforms has been shown in ischemic preconditioning [52,53]. Moreover, involvement of PKCs in cardiac arrhythmia [54] and heart failure [55] has been recently described. In detail, activation of the epsilon isoform of PKC prevented arrhythmia post ischemic injury [56].…”
Section: Pkcs and Muscular Dystrophiesmentioning
confidence: 98%